Linguistic Awareness of Teenagers: How They Apply the Role of Punctuation in English Writing - Muhamad Sofian Hadi; Lidiyatul Izzah; Melawati Melawati (Scripta : English Department Journal, 2022)
The purpose of this research is to determine the students’ errors in using punctuation marks at Cakung East Jakarta. this research approach was descriptive quantitative method. In collecting the data, the researcher asked the students to rewrite the sentence with the right punctuation. The total population teenagers at Cakung and samples was 20 teenagers as the respondents. For the exam, The researcher discovers that the test's average score is 52.5, with 100 being the highest and 80 being the lowest possible scores. For the questioonnaire, the researcher finds the result of the questionnaire for the first statement always use a period to end statement sentence is 70% participant choose always, second statement use period in every sentence statement is 40% choose always, third statement use comma before writing a direct sentence is 35% choose sometimes, fourth statement use a comma in the middle of sentence is 40% choose often, fifth statement use quotation is 45% choose always, sixth statement exclamation point is 50% choose always, and the last use exclamation when showing a surprised expression is 45% choose always. The reason why they made erorr is because they did not know the limitation and the role of the structure and context.